Levels of vitamin D in the blood, the factors that affect it, and its relationship to repeated infections in pre-school-aged children - Havlová, Adéla; Velemínský, Miloš; Šimková, Simona (Journal of Nursing, Social Studies and Public Health, 2020)
The influence of vitamin D on calcium and phosphorus metabolism in relation to bone and muscle metabolism has been known for a long time. Lately, it seems that the effect of vitamin D has expanded. Among other things, it influences the immune system, diabetes mellitus, obesity or neuropsychiatric development. The lack of vitamin D is associated with an increased incidence of infectious diseases in children and adults. The goal of this article was to map the levels of vitamin D in the blood of pre-school-aged children, its supplementation, using creams with protective factors in winter, stays at sea, nutrition and recurrent respiratory tract infections. The research was carried out in two phases (with two sample groups) from June 2018 to March 2019. Blood samples were taken from the children in the first sample group, and these were analyzed for vitamin D levels. At the same time, their parents filled in questionnaires (N = 31). The blood samples from the children in the second sample group (N = 61) were analyzed for the relationship between vitamin D levels and recurrent respiratory tract infections. We proved the importance of supplementation on vitamin D levels. We discovered that 56.5% of children without supplementation suffered from severe or mild vitamin D deficiency, and 25% of children with supplementation had a slight deficiency. We also partly proved the positive influence of solar radiation and the use of creams with UV protective factors on vitamin D levels. We also proved a relationship between low levels of vitamin D and respiratory diseases in children. 23% of children with recurrent respiratory tract infections had a mild or severe deficiency of vitamin D. Our results are limited by a low number of examinations and also by the fact that this study is retrospective.
Keywords: recidiva; Recurrence; předškolní dítě; Vitamin D Deficiency; Humans; lidé; vitamin D; Child, Preschool; Respiratory Tract Infections; Vitamin D; nedostatek vitaminu D; infekce dýchací soustavy